Pedagogical Approaches for Improving English Pronunciation in Higher Secondary School Students - Zarmina Ghouri; Muhammad Adnan Riaz; Rohina Batool; Yusra Irfan (Review Journal of Social Psychology & Social Works, 2025)
The primary aim of English education is to enable pupils to communicate proficiently. Teachers place a strong emphasis on vocabulary and grammar, and pronunciation is kept at low priority. This study examined the viewpoints of secondary school English instructors concerning pronunciation and its instruction, along with their individual techniques in teaching pronunciation. The study was descriptive, focusing on thirteen public higher secondary schools, which were the sole accessible institutions. A cohort of thirty-nine educators was chosen for data collecting. A semi-structured interview and an observational checklist were created in accordance with the study objectives and enquiries. These instruments were administered to all 39 educators from government higher secondary schools. Pilot testing was performed on thirteen teachers not included in the sample group to verify the reliability of the instruments. Validity was improved by expert evaluations, and multiple items were modified according to their suggestions. The researcher conducted on-site visits to the schools to gather data, having obtained prior authorization from the respective administrations. Research indicated that educators utilized effective pedagogical strategies to promote clear and consistent pronunciation, highlighting the need of delivering feedback and correction to facilitate student advancement. Consistent practice and repetition were emphasized as essential for enhancing pronunciation skills. Nevertheless, the study determined that although educators exhibited a robust basis in language education, they frequently did not execute these tactics effectively in their classrooms. It is advisable to improve English language acquisition by embedding pertinent situations in English textbooks, integrating technology, and employing pronunciation applications or online resources for supplementary practice.